2007
DOI: 10.1002/polb.21134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interface on thermodynamic behavior of liquid crystalline type amphiphilic di‐block copolymers

Abstract: In PEO m -b-PMA(Az) n amphiphilic diblock copolymers, nanoscale structures exhibit an hexagonal-packed PEO m cylinders arrangement. To precisely investigate the role of interfacial interactions between hydrophilic PEO m and hydrophobic PMA(Az) n including mesogene sequences in the side chains, at the isotropic transition, polymer systems are submitted to thermal and barometric effects under hydrostatic pressure. The thermodynamic investigation is based on the original coupled calorimetric-PVT technique, yieldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…During annealing at reasonably lower temperature than the glass transition temperature (T g ), the system tends to evolve towards lower energetic states and to get closer to a virtual equilibrium state. 6,11,12 The pressure sensitivity was illustrated in situ during polymer phase transitions 13,14 and ex-situ on solid polymer. In this latter case, an increase of the glass transition temperature, as well as an endothermic peak located nearby T g , can be observed after annealing.…”
Section: Introductionmentioning
confidence: 99%
“…During annealing at reasonably lower temperature than the glass transition temperature (T g ), the system tends to evolve towards lower energetic states and to get closer to a virtual equilibrium state. 6,11,12 The pressure sensitivity was illustrated in situ during polymer phase transitions 13,14 and ex-situ on solid polymer. In this latter case, an increase of the glass transition temperature, as well as an endothermic peak located nearby T g , can be observed after annealing.…”
Section: Introductionmentioning
confidence: 99%
“…In complete contrast, ΔS tr increases when the pressure is exerted by N 2 and CO 2 . In this respect, as observed above, N 2 is a "neutral" fluid as compared to "chemically active" CO 2 , and consequently the large increase of ΔS tr shows that the organization of nanostructures is the easiest the more "active" is the fluid, in particular when the fluid is in supercritical state [32][33][34]. The influence of the pressure-transmitting fluid on the transition entropy at the interface is well illustrated by the increase of the Clapeyron slope (dT/dp) tr in the sequence Hg < N 2 < CO 2 as shown Fig.…”
Section: Role Of High-pressure Gas On Molecular Self-assembled Organimentioning
confidence: 57%
“…Regarding nanoscale self-assembled molecular organization in liquid crystallinetype amphiphilic diblock copolymers, the use of T CST is well described [6,10,11] by the systematic investigation of PEO m -b-PMA(Az) n type polymers (with m and n degrees of polymerization) containing hydrophilic polyethylene oxide (PEO) and hydrophobic azophenyl (PMA(Az)) moieties. Isobaric scans over the isotropic transition of PEO 114 -b-PMA(Az) 20 using either mercury or supercritical CO 2 as pressurizing fluids demonstrated that "inert" mercury and "chemically active" CO 2 have quite opposite effects on the Clapeyron slope of this transition.…”
Section: Figmentioning
confidence: 99%